Optimization of the expression of surface antigen SAG1/2 of Toxoplasma gondii in the yeast Pichia pastoris - Thiruvengadam, G.; Ithoi, Init; Fong, Mun Yik; Lau, Yee Ling (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Surface antigens are the most abundant proteins found on the surface of the parasite Toxoplasma gondii. Surface antigen 1 (SAG1) and Surface antigen 2 (SAG2) remain the most important and extensively studied surface proteins. These antigens have been identified to play a role in host cell invasion, immune modulation, virulence attenuation. Recombinant SAG1/2 was cloned and expressed in yeast Pichia pastoris. We describe here optimization of critical parameters involved in high yield expression of the recombinant SAG1/2. Our results suggest that recombinant SAG1/2 were best expressed at 30ÂºC, pH 6 and 1 methanol as the carbon source by X33 Pichia cells. Additional optimizations included the downstream process such as ammonium sulphate precipitation and dialysis. The fusion protein was purified using Ni-NTA purification system with 80 recovery. The purified protein was 100 specific and sensitive in detection of toxoplasmosis.